Distribution and transmission of Mycobacterium tuberculosis complex lineages among children in peri-urban Kampala, Uganda - Wampande, Eddie M.; Mupere, Ezekiel; Jaganath, Devan; Nsereko, Mary; Mayanja, Harriet K.; Eisenach, Kathleen; Boom, W. Henry; Gagneu, Sebastien; Joloba, Moses L. (BMC pediatrics, 2015)
To gain insight into the transmission of tuberculosis (TB) in peri-urban Kampala-Uganda, we performed a household contact study using children as a surrogate for recent transmission of Mycobacterium tuberculosis (MTB). Using this approach, we sought to understand M. tuberculosis complex (MTBC) lineage diversity, distribution and how these relate to TB transmission to exposed children. Method: MTBC isolates from children aged ≤ 15 years, collected from 2002 to 2010 in a household-contact study, were analyzed using a LightCycler RT-PCR SNP genotyping assay (LRPS). The resultant genotypic data was used to determine associations between MTBC lineage and the children’s clinical and epidemiological characteristics. Results and discussion: Of the 761 children surveyed, 9 % (69/761) had culture-positive TB an estimate in the range of global childhood TB; of these 71 % (49/69) were infected with an MTBC strain of the “Uganda family”, 17 % (12/69) infected with MTBC lineage 4 strains other than MTBC Uganda family and 12 % (8/69) infected with MTBC lineage 3, thereby disproportionately causing TB in the study area. Overall the data showed no correlation between the MTBC lineages studied and transmission (OR = 0.304; P-value = 0.251; CI: 95 %; 0.039-2.326) using children a proxy for TB transmission. Conclusions: Our findings indicate that MTBC Uganda family strains are the main cause of TB in children in peri-urban Kampala. Furthermore, MTBC lineages did not differ in their transmissibility to children.
Keywords: Household; Childhood tuberculosis; Transmission; MTBC lineages